Contestation with the Bio-Power in Normalizing Process: The Life Experiences of Families with Autistic Children - Theerasilp, Ubonpun; Sherer, Penchan (Kasetsart Journal of Social Sciences, 2014)
This study aimed to study the striving for normalcy of families with autistic individuals by using Foucault’s postmodern framework of disability and the bio-medical model of autism. The methodology was a qualitative study that emphasized a participatory approach and in-depth interviews that focused on the intersubjectivity of meanings of autism. The findings indicated that the mainstream explanation of autism was based on a bio-medical model, viewing autism as an impairment to be corrected by medical intervention. Families hoped that medical treatment would provide normalization processes resulting in their children being able to study in an inclusive educational system. Many families had experienced dealing with abuse of authority, stigmatization, and discrimination. Some families had suffered from, and were willing to comply with, the requirements of professional authorities for a while, before refusing further intervention. This study argued that the biomedical model does not provide the absolute answer to caring for the autistic individuals and their families. This study recommended a more humanistic approach throughout the therapeutic process and social understanding to create an inclusive society by accepting the identity of autistic individuals and giving them the opportunity to present themselves as they are, even though their deficit cannot be corrected.